Systematization of nursing care based on CIPE® and the theory of adaptation in hypertensives - Denizielle de Jesus Moreira Moura; Maria Célia de Freitas; Maria Vilani Cavalcante Guedes; Marcos Venícius de Oliveira Lopes; Luciana Catunda Gomes de Menezes; Ariane Alves Barros (Universidade Federal de Goias, 2014)
Study aimed to identify diagnoses and plan outcomes and interventions based on the CIPE® nomenclature and on the theory of adaptation to hypertensive patients with associated diseases. It is a multiple case study conducted with 45 users of the Family Health Strategy and registered in HIPERDIA. The most frequent diagnoses identified were partial self-care (93.3%), decreased exercise pattern (84.4%), impaired dentition (82.2%), and low learning process (60%). Outcomes and interventions aimed at improving adherence to treatment and quality of life were planned for these diagnoses. The results of this study highlight the need for care of hypertensives with complications, supporting a theoretical foundation and practice of nursing care through the development of statements of diagnoses, outcomes, and interventions. doi: 10.5216/ree.v16i4.22945.